A Comprehensive Review of Thermal Management Methods and Ideal System Design for Improved Electric Vehicle Battery Pack Performance and Safety - M. Murugan; P. V. Elumalai; KCK Vijayakumar; M. Babu; K. Suresh Kumar; M. Ganesh; Liu Kuang; S. Prabhakar (Energy Science & Engineering)
ABSTRACT The scientific aim of the study is to propose a comprehensive review of thermal management systems (TMSs) used in electric vehicle (EV) battery packs on matters pertaining to performance enhancement, improvements in safety, and reliability. This includes the various thermal management strategies, addressing some of the problems posed by the dynamic nature of operating conditions, and evaluating emerging TMS technologies. From this aspect, the problem of this research focused on the description of a detailed insight into the efficiencies of TMSs inside an EV, pointing to the impacts of various cooling mechanisms, mostly liquid cooling, air cooling, and phase‐change materials. The research study further evaluates the integration of TMS in vehicle design and its effects on battery lifespan, charging speeds, and environmental impacts. The benefits, disadvantages, and specific applications of each method are discussed about EVs. Taking into consideration the fast charging, high‐power, and environmental effects, further discussion is made on the specific challenges that come with dynamic operating conditions of EVs. This is shown through the industry's constant pursuit to develop in this critical area through the discovery of novel technologies, including predictive control algorithms and superior thermal materials. It discusses in depth how heat management is integrated into the general vehicle design and how this impacts battery lifespan, charging speed, and range. In conclusion, it is a source of material for research scholars, engineers, and policymakers in charge of developing EVs by synthesizing what already exists, highlighting trends at current times, and outlining possible future directions in the continuum of optimizing TMS for the next generation of driving automobile transportation batteries.